Phân tích đa thức thành nhân tửA=a(b^2+c^2)+b(a^2+c^2)+c(a^2+b^2)+3abc
Phân tích đa thức thành nhân tửA=a(b^2+c^2)+b(a^2+c^2)+c(a^2+b^2)+2abc
Phân Tích Đa Thức thành nhân tử 3abc+a^2(a-b-c)+b^2(b-a-c)+c^2(c-a-b)-c(b-c)(a-c)
Phân tích đa thức thành nhân tử: 2 * (a^2 * c + b^2 * a + c^2 * b ) - ( a^2 * b + b^2*c +c^2 * a)- 3abc
phân tích thành nhân tử
a)(x+1)(x+2)(x+4)(x+5)-40
b)a²b²(a-b)+b²c²(b-c)+c²a²(c-a)
c)a³+b³+c³-3abc
\(a,=\left[\left(x+1\right)\left(x+5\right)\right]\left[\left(x+2\right)\left(x+4\right)\right]-40\\ =\left(x^2+6x+5\right)\left(x^2+6x+8\right)-40\\ =\left(x^2+6x\right)^2+13\left(x^2+6x\right)+40-40\\ =\left(x^2+6x\right)^2+13\left(x^2+6x\right)=\left(x^2+6x\right)\left(x^2+6x+13\right)\\ b,=a^2b^2\left(a-b\right)+b^2c^2\left(b-a+a-c\right)+c^2a^2\left(c-a\right)\\ =a^2b^2\left(a-b\right)-b^2c^2\left(a-b\right)-b^2c^2\left(c-a\right)+c^2a^2\left(c-a\right)\\ =\left(a-b\right)\left(a^2b^2-b^2c^2\right)-\left(c-a\right)\left(b^2c^2-c^2a^2\right)\\ =b^2\left(a-b\right)\left(a-c\right)\left(a+c\right)-c^2\left(c-a\right)\left(b-a\right)\left(b+a\right)\\ =\left(a-b\right)\left(a-c\right)\left[b^2\left(a+c\right)-c^2\left(b+a\right)\right]\\ =\left(a-b\right)\left(a-c\right)\left(a^2b+b^2c-b^2c+a^2c\right)\\ =a^2\left(a-b\right)\left(a-c\right)\left(b+c\right)\)
\(c,=\left(a+b\right)^3-3ab\left(a+b\right)+c^3-3abc\\ =\left(a+b+c\right)\left(a^2+2ab+b^2-ac-bc+c^2\right)-3ab\left(a+b+c\right)\\ =\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ac\right)\)
Phân tích đa thức thành nhân tử:
2 * (a^2 * c + b^2 * a + c^2 * b ) - ( a^2 * b + b^2*c +c^2 * a)- 3abc
Phân tích đa thức thành nhân tửA=8abc+4(ab+bc+ca)+2(a+b+c)+1
A = 8abc + 4ab + 4bc + 4ca + 2a + 2b + 2c + 1
Phân tích đa thức thành nhân tử: 2.(a2c + b2a + c2b ) - ( a2b + b2c +c2a)- 3abc
Phân tích đa thức thành nhân tử: 2.(a2c + b2a + c2b ) - ( a2b + b2c +c2a)- 3abc
Phân tích đa thức thành nhân tử: 2.(a2c + b2a + c2b ) - ( a2b + b2c +c2a)- 3abc